2000
DOI: 10.1118/1.1328383
|View full text |Cite
|
Sign up to set email alerts
|

Monitor unit settings for intensity modulated beams delivered using a step‐and‐shoot approach

Abstract: Two linear accelerators have been commissioned for delivering IMRT treatments using a step-and-shoot approach. To assess beam startup stability for 6 and 18 MV x-ray beams, dose delivered per monitor unit (MU), beam flatness, and beam symmetry were measured as a function of the total number of MU delivered at a clinical dose rate of 400 MU per minute. Relative to a 100 MU exposure, the dose delivered per MU by both linear accelerators was found to be within +/-2% for exposures larger than 4 MU. Beam flatness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 23 publications
2
50
0
1
Order By: Relevance
“…The gamma passing rates were greater than 99% for all of the gating windows and energies using 1 mm and 2% criteria. These findings were comparable to those obtained using a step‐and‐shoot delivery technique 13. However, with stricter agreement criteria of 1%/1mm, the gamma score decreased slightly to 97.66% (Table 2) for 6 MV and ~92% for 10 MV and 18 MV.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The gamma passing rates were greater than 99% for all of the gating windows and energies using 1 mm and 2% criteria. These findings were comparable to those obtained using a step‐and‐shoot delivery technique 13. However, with stricter agreement criteria of 1%/1mm, the gamma score decreased slightly to 97.66% (Table 2) for 6 MV and ~92% for 10 MV and 18 MV.…”
Section: Resultssupporting
confidence: 82%
“…When commissioning a system for gated radiotherapy, it is important to characterize the startup characteristics of the accelerator 13. This is true because gated radiotherapy introduces delivery situations not typically encountered in external beam radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Our results lie within the recommended levels. Several authors have reported the dosimetric characteristics of linear accelerator therapy systems at low MU settings [9]- [14]. Das et al reported dose errors higher than 20% for the first few MUs, which stabilize within 5% at MUs exceeding 10 [10].…”
Section: Discussionmentioning
confidence: 99%
“…As DMLC and VMAT are unavailable in the current commercial version of Vero4DRT, the system should be operated in the step-and-shoot IMRT mode. In previous reports, when step-and-shoot IMRT was implemented with several low monitor units (MUs) per segment at high dose rates, the dosimetric errors were large [9]- [14]. Among researchers who investigated the beam characteristics at low MU settings, Das et al reported a dosimetric error exceeding 20% [10], and Ravikumar et al measured the deviation in dose delivery as 20% -25% (using 6 and 18 MV photon beams at low MU setting) [11].…”
Section: Introductionmentioning
confidence: 99%
“…( 14 16 ) This is because the step‐and‐shoot technique sometimes uses so many small sized segments with associated monitor units (MUs). ( 17 , 18 ) Moreover, the delivered dose accuracy can be affected by the accuracy of the leaf positioning, (19) the overshoot effect, (20) and dose nonlinearity for small MU delivery (21) . With more and more external treatment‐planning systems and LINAC support of IMRT delivery using the sliding window technique, more studies regarding the dosimetry and mechanical modulation such as the leaf speed are needed.…”
Section: Introductionmentioning
confidence: 99%